Effect of ondansetron for preventing of ovarian hyperstimulation syndrome: in an experimental rat model - Şükrü Bakırcı; Nevin Sağsöz; Tuba Devrim; Yaşar Şahin; Murat Bulanık; Hilal Gözüyukarı (Gynecological Endocrinology)
Objective: Ovarian hyperstimulation syndrome is an iatrogenic condition that occurs in the treatment of infertility. There is no specific treatment available for OHSS. Cabergoline is a dopamine receptor 2 agonist and VEGF-VEGF2 receptor antagonist . Recently, cabergoline has been widely used to prevent the development of OHSS and reduce its severity Serotonin is known as a neurotransmitter and thought to have a role in the mechanism of angiogenesis and in signaling in endothelial cells. Serotonin is said to have similar effects to VEGF . Ondansetron is Selective Serotonin (5-HT3) Receptor Antagonist . It works by blocking the action of serotonin, a natural substance that may cause nausea and vomiting. In the clinical practice today, there is no choice other than cabergoline, to prevent occurrence and reduce severity of OHSS, and sometimes its effects are limited. Methods: In our study, we compared the effect of cabergoline and ondansetron. 32 immature rats were used and the OHSS model was created. Parameters such as hematocrit value , ovarian size, the number of follicles in the ovary, endometrial capillary congestion and thickness values were evaluated and compared. Results: As a result, in our study, it was seen that ondansetron was effective on OHSS in many parameters. It is thought to be as effective as cabergoline. When we look at the literature, this is the first study in which ondansetron was evaluated for this purpose. It would be good to show this effect of ondansetron with other studies.